ANALISIS KOMPARATIF EARNINGS MANAGEMENT PADA PERUSAHAAN FORCED DAN VOLUNTARY DELISTING PADA BURSA EFEK INDONESIA - Winne Carissa Hidayat; Sahala Manalu; Rony Joyo Negoro Octavianus (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2015)
From 2005 until early 2015, as many as 52 companies perform delisting. Meanwhile, the practice of earnings management will be found on all companies including the delisted companies. Previously earnings management are found on discretionary accruals, but because it is often used and can be detected easily managers began to switch to manipulate earnings through operating activities or real activities manipulation. The purpose of this study is to analyze the practices of earnings management through real activities manipulation in companies that perform forced and voluntary delisting. Obtained each of 14 companies forced and voluntary delisting during observation from 2005 to 2014 who meet the criteria of purposive sampling. The results using independent t-test found there were no difference in the average earnings management in forced and voluntary delisting companies, which in both earnings management done to lower profits. It is analyzed as the company's goals for the restructuring of debt, save on tax payments as well as the distribution of dividends and employee bonuses. Thus, earnings management to do more to efficient contracting perspective